Islamic Management and Leadership in the PKS Party Organization (Communication Process between Leaders and Members, Communication Principles, Communication Barriers, Use of Oral, Written and Verbal Communication) in Padangsidimpuan - Napitupulu, Pija; Syafnan, Syafnan; Siti Rahma Dongoran; Subuh Waldo Huakbar (RADINKA JAYA UTAMA PUBLISHER, 2024)
The purpose of this study is to investigate the principles of communication applied in the organization, identify barriers that arise during the communication process, and analyze the use of written and oral communication. The research method used in qualitative research with a focus on phenomena. The findings of the study indicate that communication is an important aspect of all social interactions, especially when people have strong ties with each other. The Prosperous Justice Party is a political party with a strong communication approach that includes mass, social, group, personal, and democratic communication. PKS uses various communication models to engage the public, including mass media, social media, group communication, door-to-door communication, and democratic communication. The Social Justice Party also uses the principles of social communication, such as the active participation of the general public, the use of contemporary media, and democratic communication. This strategy helps the Social Justice Party increase public trust, increase cadre loyalty, and achieve effective political goals. The integration of the principle of da'wah into all political activities ensures that all efforts are not only to protect the political environment but also to promote and integrate the general public with Islamic principles. Public communication is an important component of the Social Justice Party's communication strategy. The final step in the Social Justice Party's reform process is the development of a clear and structured program for the general public. This approach ensures that the Social Justice Party effectively communicates its values and interests to the public, ultimately resulting in better public relations and governance.